Shared genetic architecture between grip strength and cognitive function: insights from large-scale genome-wide cross-trait analysis - Liu, Hong; Wu, Gangqiang; Tan, Jun; Yuan, Chunyun (Frontiers in Genetics, 2025)
BackgroundPhysical and cognitive decline are common in older individuals, and traits related to grip strength and cognitive function are used to assess the common genetic structure between the two and to identify common risk loci and genes as well as the genetic mechanisms involved.MethodsOn the basis of large-scale genome-wide association study (GWAS) summary-level datasets, we observed genetic overlaps between grip strength and cognitive function, and cross-trait pleiotropic analysis was performed to detect shared pleiotropic loci and genes. A series of functional annotations and tissue-specific analyses were performed to determine the influence of pleiotropic genes. Heritance enrichment analysis was used to detect crucial immune cells and tissues. Finally, drug targets were explored via the SMR method.ResultsThis study highlighted genetic mechanisms shared between five types of cognitive function-related traits and grip strength. This study identified 20 novel SNP loci (P < 5 × 10−8/5) and 7 pleiotropic genomic risk loci, of which 1p34.2 and 4q24 have been shown to be associated with trait pairs in previous studies. Furthermore, 7 unique pleiotropic genes, such as BANK1, CADM2, AFF3 and AUTS2, were identified at the gene level. Four drug targets in European populations were identified via PLACO analysis combined with FUMA, MAGMA and SMR results, which were consistent with the pleiotropic genetic results and were novel. Finally, the immune mechanisms of trait pairs were validated via HyPrColoc.ConclusionOverall, our results provide new insights into the genetics of cognitive function and grip strength and shed light on the underlying molecular mechanisms that may be involved.